The Description of Postpartum Mother’s Knowledge About The Benefit of Oxytocin Massage in Regards To Multiply The Breast Milk Productivity at Romana Clinic 2022 - Ermawaty Arisandi; Marissella Situmorang; Desriati Sinaga; Bernadetta Ambarita (Institute of Computer Science (IOCS), 2022)
Oxytocin massage is a massage along the spine (vertebrae) to the fifth or sixth rib. Knowledge of postpartum mothers about the benefits of oxytocin massage will affect breastfeeding to babies, breast milk that does not come out will cause the baby's weight to decrease because the baby's daily needs are not fulfilled properly. This study aims to describe the knowledge of postpartum mothers about the benefits of oxytocin massage in increasing breast milk production at the Romana Clinic 2022. This study used a descriptive method. The sample in this study was postpartum mothers 0-42 days who made postpartum visits at the Romana Clinic in 2022 with a total of 32 respondents. Researchers used primary data. The results of the study are as follows: from 32 respondents, the majority have sufficient knowledge as many as 17 people (53.125%), lack of knowledge as many as 11 people (34.375%), and the minority with good knowledge as many as 4 people (12.50%). Conclusion: Based on the results of the study, it shows that the higher the education of the mother, the higher the knowledge about the benefits of oxytocin massage.